Terms of Choice: Uncertainty, Journalism, and Crisis. (28th April 2015) - Zelizer, Barbie
Abstract This article considers whether thinking about journalism's present set of challenges is best served by the notion of "crisis." It argues that adopting such a notion to explain a diverse set of technological, political, economic, social, occupational, moral, and legal circumstances misses an opportunity to recognize how contingent and differentiated the futures of journalism might be. It also raises critical questions about how institutions deal with uncertainty at their core, obscuring a fuller understanding of the permutations that get eclipsed by perceiving crisis as a unitary phenomenon.